Eksistensi Pendidikan Diniyah: Upaya Mengatasi Degradasi Moral di Masyarakat - Mainuddin Mainuddin (JIE (Journal of Islamic Education), 2023)
This research aims to discover what causes moral degradation and how madrasah diniyah as an educational institution provides a solution. This research uses a literature study, including qualitative analysis. The data used in this study will be sourced from various literature, including books, journals, articles, and academic sources related to the existence of diniyah education and moral degradation in society. The data that has been collected will be analyzed descriptively and qualitatively. The results of this study show that Madrasah Diniyah plays an essential role in overcoming moral degradation in society. Moral education can be done by applying exemplary and habitual education. These strategies should enable Madrasah Diniyah to overcome existing ethical problems and contribute to developing a morally upright generation.